PERAN GURU MENGATASI PENGARUH GADGET PESERTA DIDIK KELAS V DI MIS AT TAQWA SAMBAS TAHUN AJARAN 2023-2024 - Yuniarti; Sumar’in; Asyruni Multahada (CV. Adiba Aisha Amira, 2026)
This study aims to analyze the influence of gadgets on fifth-grade students at MIS At Taqwa Sambas and the teacher's role in addressing it. The digital era has presented new challenges for the education sector, where gadget usage provides ambivalent impacts on student development. This research employs a qualitative approach with phenomenological research design. Data collection was conducted through participant observation, unstructured interviews with fifth-grade teachers and students, and documentation. Data analysis utilized the Miles and Huberman model consisting of data reduction, data presentation, and conclusion drawing. The results indicate that gadgets provide positive influences including increased learning interest through educational applications, interactive learning media, and communication facilitation. However, negative impacts such as learning focus disruption, exposure to inappropriate content, and gadget addiction leading to antisocial behavior were also identified. Teachers play strategic roles in five main dimensions: as guides who establish usage rules, educators who integrate gadgets in interactive learning, coordinators who collaborate with parents, counselors who provide wise usage guidance, and knowledge providers about digital literacy. The success of gadget utilization in education depends on teachers' ability to optimally perform their multidimensional roles and solid collaboration between schools and families in supervising and guiding students' gadget usage.